Le notti dell’isteria - Fagioli, Massimo (Il sogno della farfalla, 2008)
This writing, which has been written for the exhibition “L’Italie aujourd’hui” held in Nice in June 1985 and was published in the same year, presents in narrative style a profound critique of Marxism, Freudism and the ideologies of 1968.